Sociology of education a critical reader - Sadovnik, Alan R. (Routledge, 2011)
Examines the various topics in sociology and education while exposing students to examples of sociological research on schools. This title intends to stimulate student thinking about the important roles that schools play in contemporary society and their ability to solve fundamental social, economic and political problems.